2014
DOI: 10.1097/01.aud.0000436923.96492.3a
|View full text |Cite
|
Sign up to set email alerts
|

Longer-Term Functional Outcomes and Everyday Listening Performance for Young Children Through to Young Adults Using Bilateral Implants

Abstract: Overall, the results indicate primarily positive functional outcomes for children and young adults receiving bilateral implants at all ages, including when the delay between implants is long. The results are important for evidence-based preoperative counseling, which helps families to make informed decisions and develop appropriate expectations. The results are also important for the development of clinical management practices that support and encourage the minority of recipients who have difficulty adapting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…This result is consistent with those of previous studies in which parents, teachers and adolescents have all identified group conversations as particularly difficult for CI users, with some emphasising the additional difficulties caused by the presence of background noise (Bat-Chava & Deignan, 2001;Rich et al, 2013;Wheeler et al, 2007). The significantly higher performance ratings in the BiCIs condition for the present children in group conversations are consistent with previous anecdotal reports that children function better and are more confident in group communication when using BiCIs (Galvin et al, 2014;Redfern & McKinley, 2011), and with parent reports that the use of BiCIs predicts positive communication, social, and academic outcomes, including participation in a mainstream classroom (Hyde et al, 2011). The importance of an improved ability to participate in group conversations cannot be overestated.…”
Section: Discussionsupporting
confidence: 92%
“…This result is consistent with those of previous studies in which parents, teachers and adolescents have all identified group conversations as particularly difficult for CI users, with some emphasising the additional difficulties caused by the presence of background noise (Bat-Chava & Deignan, 2001;Rich et al, 2013;Wheeler et al, 2007). The significantly higher performance ratings in the BiCIs condition for the present children in group conversations are consistent with previous anecdotal reports that children function better and are more confident in group communication when using BiCIs (Galvin et al, 2014;Redfern & McKinley, 2011), and with parent reports that the use of BiCIs predicts positive communication, social, and academic outcomes, including participation in a mainstream classroom (Hyde et al, 2011). The importance of an improved ability to participate in group conversations cannot be overestated.…”
Section: Discussionsupporting
confidence: 92%
“…When compared with an older implanted group (>3.5 years; n = 32), significantly more parents in a younger-implanted group (≤3.5 years; n = 25) reported a positive outcome on each of the measures of: adaptation to BiCIs, BiCI usage, device preference, attitude towards the second implant, and performance with each implant alone (χ 2 ≥ 4.71, P ≤ 0.03). A detailed description of this data was presented in Galvin et al (2014).…”
Section: Resultsmentioning
confidence: 99%
“…If we had included children with a wider range in inter-implant delay, this factor might have been significant. For example, Galvin et al [16] showed that, in contrast to the whole study group, in a large group of children with various inter-implant delays, no significant effect of inter-implant delay on ease of adaptation was found when the children who were implanted simultaneously were left out of the analysis. Furthermore, in the children and adolescents in the study of Illg et al [9], inter-implant delay had a significant influence on speech comprehension with the CI2.…”
Section: Discussionmentioning
confidence: 96%
“…To our knowledge, however, the effect of device use on auditory brainstem maturation has never been investigated. On average, we know that approximately 25-35% of the children implanted sequentially are not full-time CI2 users [11,16,17]. When this factor is taken into account, the critical period for sequential bilateral cochlear implantation might be extended.…”
Section: Introductionmentioning
confidence: 97%